2022
DOI: 10.1007/s11409-022-09307-w
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive judgments can potentiate new learning: The role of covert retrieval

Abstract: Interim tests of previously studied information can potentiate subsequent learning of new information, in part, because retrieval-based processes help to reduce proactive interference from previously learned information. We hypothesized that an effect similar to this forward testing effect would also occur when making judgments of (prior) learning (JOLs). Previous research showed that making JOLs likely prompts covert retrieval attempts and thereby enhances memory, specifically when providing only parts of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
3
8
0
Order By: Relevance
“…Another relevant question for follow-up research is how our manipulation influenced the processing of the answer options and feedback presented. Retrieval processes (including uninstructed covert retrieval) can enhance not only the retention of the practiced information but also subsequent studying of learned and new information (e.g., Kubik, Koslowski, et al, 2022). Therefore, benefits of the stepwise display and/or competitive answer options, may to some extent be driven by learners’ enhanced processing of answer options and feedback presented after the retrieval opportunity (so-called test-potentiated encoding or indirect testing effects, e.g., Arnold & McDermott, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant question for follow-up research is how our manipulation influenced the processing of the answer options and feedback presented. Retrieval processes (including uninstructed covert retrieval) can enhance not only the retention of the practiced information but also subsequent studying of learned and new information (e.g., Kubik, Koslowski, et al, 2022). Therefore, benefits of the stepwise display and/or competitive answer options, may to some extent be driven by learners’ enhanced processing of answer options and feedback presented after the retrieval opportunity (so-called test-potentiated encoding or indirect testing effects, e.g., Arnold & McDermott, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Following previous JOL reactivity studies (Kubik et al 2022;Li et al 2023Li et al , 2024, the current experiment employed a within-subjects design (JOL vs. no-JOL). Participants were informed that they would study four lists of words in preparation for a later memory test.…”
Section: Methodsmentioning
confidence: 99%
“… Jönsson et al ( 2012 ) suggested that this facilitation is related to the covert retrieval attempts of the target information resulting from the delayed JOL, which itself facilitates learning and is often referred to as the retrieval practice effect ( McDaniel et al 2007 ; Karpicke and Roediger 2008 ; Carpenter et al 2008 ; Hausman and Rhodes 2018 ). In other words, when individuals make metacognitive judgments, they engage in covert retrieval attempts to predict their own test performance ( Kubik et al 2022 ). Thus, compared to restudy, one of the most common learning strategies without any item retrieval, delayed JOL can more effectively promote learners’ memory for learned items.…”
Section: Introductionmentioning
confidence: 99%
“…The current research focuses on the forward effects of delayed JOL, which are receiving increasing attention as an indirect but future-oriented benefit of delayed JOL. Recent studies have found that delayed JOL not only promotes the retention of previously learned information, but also has a positive effect on the subsequent learning of new material ( Lee and Ha 2019 ; Kubik et al 2022 ). To examine the forward effect of JOL, methods were developed based on the paradigm of the forward test effect (FTE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation